2014
DOI: 10.1186/1472-6882-14-395
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolic, flavonoid contents, in-vitro antioxidant activities and hepatoprotective effect of aqueous leaf extract of Atalantia ceylanica

Abstract: BackgroundDecoction prepared from leaves of Atalantia ceylanica is used in traditional medicine in Sri Lanka for the treatment of various liver ailments since ancient times. Lyophilized powder of the water extract of A. ceylanica leaves was investigated for its phytochemical constituents, antioxidant and hepatoprotective activity in-vitro.MethodsThe total phenolic and flavonoid contents were determined using Folin Ciocalteu method and aluminium chloride colorimetric assay respectively. The antioxidant activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…The hepatoprotective activity of Morus nigra could be attributed to the presence of chemical compounds that are biologically active. Phytochemical screening demonstrated that plant contains hepatoprotective phenols, flavonoids, alkaloids and terpenoids (Fernando, Soysa, 2014). Qualitative analysis by isocratic flow HPLC showed the presence of six phytoconstituents in n-hexane extract of leaves of Morus nigra and these findings are consistent with previous investigations (Wang, Wang, Chen, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…The hepatoprotective activity of Morus nigra could be attributed to the presence of chemical compounds that are biologically active. Phytochemical screening demonstrated that plant contains hepatoprotective phenols, flavonoids, alkaloids and terpenoids (Fernando, Soysa, 2014). Qualitative analysis by isocratic flow HPLC showed the presence of six phytoconstituents in n-hexane extract of leaves of Morus nigra and these findings are consistent with previous investigations (Wang, Wang, Chen, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Total phenolic content Folin Ciocalteu method [15] Total flavonoid content Colorimetric assay based on intensity of colour change of the mixture [16,17] Measurement of inhibiting capacity of RBCs hemolysis by ROS inducing oxidative stress [24] In-vivo assay CAT activity assay Quantifying the activity of enzymes responsible for suppressing ROS generation such as-catalase (CAT) and superoxide dismutase (SOD) in animal model treated with sample [25,26] SOD activity assay…”
Section: Assay Of Non-enzymatic Antioxidant Compoundsmentioning
confidence: 99%
“…Then absorbance was measured by UV/visible spectrophotometer at 510 nm and the values were read from catechin standard curve (y = 0.0004x − 0.0058; R 2 = 0.998). Total flavonoid content was calculated as catechin equivalent (CE) (mg/g) [16].…”
Section: Total Flavonoid Contentmentioning
confidence: 99%
“…After decades of endeavors, scientists have found that flavonoids possess a wide variety of biological and pharmacological properties, which leads to numerous studies on these secondary metabolites. These health-beneficial properties include antiangiogenic [22], antibacterial [23][24][25][26][27] [67], leishmanicidal [68], neuroprotective [69], photoprotective [43], and trypanocidal activities [68,70]. In addition, the flavonoids can inhibit eukaryotic protein synthesis [71] and a variety of important enzymes such as aggrecanase [72], aldose reductase [30,73], alpha-glucosidase [60], cholinesterase [26,74], protein tyrosine phosphatase and acetylcholinesterase [75], and tyrosinase [44,64].…”
Section: Classification and Biological Activities Of Flavonoidsmentioning
confidence: 99%